Rhipicephalus microplus (Acari: Ixodidae) parasitizing Axis axis (Artiodactyla: Cervidae) chital deer, from the Entre Ríos province, Argentina (FAVE Sección Ciencias Veterinarias, 2024)
The present research reports the finding of Rhipicephalus microplus (cattle common tick) parasitizing two exotic deer Axis axis found roadkill in two timelines (2021 and 2023) in the north of the Entre Ríos province, Argentina. Both records are found within the habitat suitability for R. microplus and constitute the first findings of parasite-host association for Argentina, as well as for the Neotropic region. This report shows the need to delve into this parasite-host association in order to determine a potential epidemiological risk.
Keywords: Rhipicephalus (Boophilus) microplus; Axis axis; exotic deer